Improving General Practitioners’ Competence in Basic Obstetric and Gynecologic Ultrasound for Early Fetal Abnormality Detection - Donel, Donel; Febriani, Febriani; Hidayatullah, Amiruddin; Ardiani, Vani; Frymonalitza, Ninda; Homaira, Kesuma Anggreini; Nugraha, Iriandanu; Hernita, Nisa Faradisa (Rifa'Institute, 2025)
In order to reduce maternal and infant mortality rates, interventions must focus on improving the quality of antenatal care, particularly at primary care level. One key competency that general practitioners must possess is the ability to perform basic obstetric ultrasound examinations to detect intrauterine foetal abnormalities early on. This community service activity aims to enhance general practitioners' skills in this area using a six-step approach. Implementation involves theoretical education, hands-on training and pre- and post-test evaluations of participants' knowledge and skills. The activity involved 30 general practitioners from the Kampar Regency area. Training results showed an average increase in post-test scores of 31.67% compared to pre-test scores, indicating significant improvements in participants' competencies. The activity also facilitated the distribution of practice- based teaching modules and strengthened collaboration with local community health centres to support maternal and child health services. Basic obstetric ultrasound training has proven to be an effective way of strengthening primary healthcare services and reducing maternal and perinatal mortality and morbidity rates.